2006
DOI: 10.1086/509044
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Desmocollin-2 Causes Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetically heterogeneous heart-muscle disorder characterized by progressive fibrofatty replacement of right ventricular myocardium and an increased risk of sudden cardiac death. Mutations in desmosomal proteins that cause ARVC have been previously described; therefore, we investigated 88 unrelated patients with the disorder for mutations in human desmosomal cadherin desmocollin-2 (DSC2). We identified a heterozygous splice-acceptor-site mutation in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
147
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(159 citation statements)
references
References 34 publications
11
147
0
1
Order By: Relevance
“…51,52 Mutations in the desmocollin-2 gene (DSC2) seem to be infrequent in ARVD/C; only five DSC2 mutations have been described to date (summarized in Figure 2E). [51][52][53] Although Dsc2 targeting in the mouse has not yet been reported, zebrafish treated with dsc2 antisense morpholino oligos demonstrated bradycardia, impaired contractility and chamber dilation. 51…”
Section: Desmocollin-2mentioning
confidence: 99%
“…51,52 Mutations in the desmocollin-2 gene (DSC2) seem to be infrequent in ARVD/C; only five DSC2 mutations have been described to date (summarized in Figure 2E). [51][52][53] Although Dsc2 targeting in the mouse has not yet been reported, zebrafish treated with dsc2 antisense morpholino oligos demonstrated bradycardia, impaired contractility and chamber dilation. 51…”
Section: Desmocollin-2mentioning
confidence: 99%
“…ARVC/D is familial in up to 50% of cases. 1,[8][9][10][11][12] Since the identification of mutations in the genes encoding the desmosomal proteins desmoplakin (DSP) 13 and plakophilin-2 (PKP2), [14][15][16][17] followed by mutations in desmocollin-2 (DSC2), 18 desmoglein-2 (DSG2) 19 and plakoglobin (JUP), 20 it has been recognised that ARVC/D is mainly a disorder of the cardiac desmosome (figure 2), a cell adhesion complex residing in the intercalated disk of cardiomyocytes. Comprehensive screening of these genes encoding the proteins of this complex leads to the identification of a pathogenic mutation in approximately 40 to 60% of ARVC/D patients.…”
Section: Netherlands Heart Journal Volume 18 Number 12 December 2010mentioning
confidence: 99%
“…Five of them encode major desmosomal proteins: plakoglobin (MIM *173325), 3,4 desmoplakin (MIM *125647), 5 plakophilin-2 (MIM *602861), 6 desmoglein-2 (MIM *125671) 7 and desmocollin-2 (MIM *125645). 8,9 The involvement of such genes led to the current idea that ARVC/D is a disorder caused mainly by defects in cell-cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…12 To date, five different DSC2 mutations have been reported: two frameshift mutations p.M477fsX480 and p. E896fsX900, 8 a heterozygous splice acceptor site mutation c.631-2A4G 9 and two missense mutations p.E102K and p.I345T. 13 In vitro functional studies showed that the two point mutations affect the intracellular localisation of DSC2a, thus suggesting a potential pathogenic effect.…”
Section: Introductionmentioning
confidence: 99%